Existence of Solutions for m-point Boundary Value Problems on a Half-Line. (17th August 2009) - Yu, Changlong; Guo, Yanping; Ji, Yude
Abstract : By using the Leray-Schauder continuation theorem, we establish the existence of solutions form -point boundary value problems on a half-linex ″ ( t ) + f ( t, x ( t ), x ′ ( t ) ) = 0, 0 < t < + ∞, x ( 0 ) = ∑ i = 1 m − 2 α i x ( η i ), lim   t → + ∞ x ′ ( t ) = 0, whereα i ∈ R, ∑ i = 1 m − 2 α i ≠ 1 and0 < η 1 < η 2 < ⋯ < η m − 2 < + ∞ are given.